Air Pollution in Central Asia (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
This article examines the issues of air pollution in the Central Asia region, which is becoming increasingly problematic. This problem is common to all humanity because all countries and populations living in all countries of the world are involved in air pollution. The article also discusses issues of air pollution in the Central Asian region.